Unveiling the role of organizational commitment on job satisfaction and job performance in Islamic education - Yaakob, Mohd Faiz Mohd; Habibi, Akhmad; Halili, Siti Hajar; Abdullah, Hamdy; Yaqin, Lalu Nurul; Alqahtani, Turki Mesfer; Fauzee, Mohd Sofian Omar (International Journal of Evaluation and Research in Education (IJERE), 2025)
This study evaluates the influences of organizational commitment components on job satisfaction and job performance among Islamic boarding school (IBS) teachers. It also aimed to decide the mediating effect of job satisfaction on the relationship between organizational commitment and job performance. This comparative study compares the path coefficient between exogenous and endogenous constructs based on respondents’ countries, Malaysia and Indonesia. Through a simple random sampling, the data were gathered from 247 respondents. The analysis was conducted through partial least square structural equation modeling (PLS-SEM) approaches (measurement model, structural model, and multi-group analysis). The measurement model informed that the obtained data was valid and reliable. The structural model examination reports that normative and continuance commitment strongly predict job satisfaction. Similarly, continuance commitment and job satisfaction are significant predictors of job performance. As a mediator, job satisfaction successfully mediates the relationships between continuance commitment and job performance and between normative commitment and job performance. No significant differences emerge from the multi-group analysis results between IBS teachers from Kedah (Malaysia) and Jambi (Indonesia), regarding all direct paths between the constructs. This article provides knowledge contributions from Indonesia and Malaysia, in the context of Islamic education.